Unpacking scaling in agricultural research for development: The role of social capital - Martinez-Baron, Deissy; Gravsholt Busck, Anne; Prager, Steven D. (Elsevier, 2024)
Agrifood systems are facing significant challenges, science and innovation are key to shift the trajectory towards ensuring sustainability and resilience. Thus, scaling assumes a critical role in agricultural research for development (AR4D). Scaling consists of a continuous process in which innovations are tailored, used, and embedded into societal dynamics adapted to various contexts, aiming to create widespread positive impacts. This systematic literature review explores scaling within the context of AR4D, with a particular focus on the role of social capital. Using bibliometric and factor analysis methods, we identified the intellectual structure in the field of scaling, revealing the knowledge domains and disciplines that have determined their emergence and growth as a scientific discipline. Then, we analyzed the role of social capital in the scaling literature. Our results showed that the field of scaling is composed by four distinct literature clusters: the innovation and adoption of agricultural technology, the economics of technology adoption, sustainability in agricultural innovations, and the emergence of scaling as a research field. Disciplines such as sustainable agriculture, systemic thinking, technological transitions, and technology adoption have contributed to the development of the field. The results indicate that the explicit consideration of social capital in the scaling literature within AR4D is limited despite the importance of relationships, trust, and reciprocity values in the process of scaling. This study highlights the continuous growth and multidisciplinary nature of scaling as a research field in AR4D, reflecting its complexity. International agricultural research centers and universities from developed countries have significantly advanced this field, also underlying the importance of locally rooted, and participatory research. Future research on the creation, development, and strengthening of social capital in scaling processes can contribute foster intentional and responsible scaling of AR4D innovations.